حكم اختلاط الأموال في المعاملات الماليّة المعاصرة – نماذج مختارة- - عمارة, محمد الصالح; عمارة, هنية (University of Eloued جامعة الوادي, 2020)
"تناول هذا البحث دراسة حكم اختلاط الأموال في المعاملات المالية المعاصرة، وذلك من خلال انتقاء بعض المسائل المتعلقة باختلاط المال الحرام بالحلال في حياتنا المعاصرة، وقد عرفنا بالمال المختلط وصوره، وأثر القاعدة الفقهية إذا اجتمع الحلال والحرام غلب الحرام، مع تبيين حكم تطهير المال المختلط، ثم تطبيقات معاصرة لاختلاط المال في البنوك الربوية والشركات المختلطة والبورصة. ولقد توصّل هذا البحث إلى نتائج أهمها: حرمة العمل والتعامل في الأماكن التي تثار حولها الشبهات إلا من باب الضّرورة، مع وجوب التخلص من الكسب الحرام المختلط بالحلال والتصدق به. وأوصى البحث بضرورة اهتمام كليات الأعمال التجارية بتدريس الجوانب المحاسبية في المؤسسات المالية، وتفعيل دور هيئات الرقابة الشرعية، وعلى البنوك ومجالس إدارتها أن يتقوا الله ويتخلصوا من الربا "This research addresses studying the provision of the mixed finances in the modern financial transactions through tackling some issues related to the mixture of halal and haram. Then, it identifies the mixed money and its types in terms of the amount including transacting with haram money and the effect of the maxim that if halal and haram money is gathered, the haram money will overwhelm, in case of equality, the jurists’ opinions about it, the way of eliminating the haram money, cleaning it, the maxim of estimating it, and its fate after being distinguished. We also demonstrate some of the mixed money applications in usurious banks, the mixed companies, and the bourses, which are suspicious establishments in terms of their legitimacy, working with, and the income gained from working with them. The research has reached several results the most important of which: the necessity of eliminating the earning mixed with haram money after cleaning it. Working in suspicious establishments is forbidden, but for the urged necessity. The haram money must be donated. The research also recommends that the faculties of commercial sciences must instruct the accounting sides within the financial establishments and enabling the legitimate controlling bodies’ role. The banks and their administrative councils must get rid of usurious money
مذكرة ماستر تخصص معاملات مالية معاصرة
Keywords: حكم الاختلاط- الأموال - المعاملات المعاصرة –البورصة -البنوك; Ruling on mixing - money - contemporary transactions - the stock exchange - banks